Impact of proposed changes in IESTI equations for short-term dietary exposure to pesticides from Australian and Codex perspective. Issue 6 (3rd June 2018) - van der Velde-Koerts, Trijntje; Margerison, Sam; Breysse, Nicolas; Lutze, Jason; Mahieu, Karin; Reich, Hermine; Rietveld, Anton; Sarda, Xavier; Sieke, Christian; Vial, Gaelle; Ossendorp, Bernadette C.
ABSTRACT: In 2015 a scientific workshop was held in Geneva, where updating the four equations for estimating the short-term dietary exposure (International Estimated Short Term Intake, IESTI) to pesticides was suggested. The impact of these proposed changes on the exposure was studied by using residue data and large portion consumption data from Codex and Australia. For the Codex data, the exposure increased by a median factor of 2.5 per commodity when changing to the proposed IESTI equations. The increase in exposure was highest for bulked and blended food commodities (case 3 equations), followed by medium-sized food commodities (case 2a equations) and small- and large-sized food commodities (case 1 and case 2b equations). For the Australian data, out of 184 maximum residue limit (MRL) large portion combinations showing acute exposures below the acute reference dose (ARfD) with the current IESTI equations, 23 exceeded the ARfD with the proposed IESTI equations (12%). The percentage exceeding the ARfD was higher for the Australian MRL large portion combinations (12% of 184) than for those of Codex (1.3% of 8, 366). However, the percentage MRL loss in the Australian dataset may not be representative of all pesticide MRLs since it concerns six pesticides only, specifically selected to elucidate the potential effects of the use of the proposed IESTI equations. For the Codex data, the increase in exposure using the proposed equations resulted in a small increased loss of 2.6% of the 1, 110 MRLs estimated by the Joint FAO/WHO Meeting on Pesticide Residues (JMPR): 1.4% of the MRLs were already not acceptable with the current equations, 4.0% of the MRLs were not acceptable with the newly proposed equations. Our study revealed that case 3 commodities may be impacted more by the proposed changes than other commodities. This substantiates one of the conclusions of the Geneva workshop to gather information on bulking and blending practices in order to refine MRL setting and dietary risk assessment for case 3 commodities where possible.